Discourse parsing of dissertation abstracts. - Heng, Hui Ying. (2008)
This study can be characterized as an attempt in analyzing the contents and structure of text, in particular, dissertation abstracts. Dissertation abstracts are usually taken for granted in many dissertation write-ups. Often, it is the abstracts that provide the information-searcher the overview of the dissertation paper itself. Just by reading the abstract, the searcher is able to identify the relevant dissertations more easily as there is usually some elementary information that must be included in the abstracts.